“Konsep Tanggung Ganda dalam Nafkah: Studi Muamalah terhadap Generasi Sandwich” - Safarudin Safarudin; Itiya Salsabela; Heni Ani Nuraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The sandwich generation phenomenon is a condition in which individuals of productive age bear the financial needs of two generations simultaneously: children who are not yet independent and elderly parents who have no source of income. This study aims to understand the real experiences of individuals who live as the sandwich generation, analyze the factors causing the double burden of income, and examine livelihood priority strategies from a muamalah perspective. The research method used was descriptive qualitative interviews with respondents who have dual responsibilities in Muslim families. The results show that economic pressures, increasing education costs, the lack of parental pension insurance, and cultural and religious values ​​regarding the obligation of birrul walidain are the main factors that place individuals in the sandwich generation position. From a muamalah perspective, the obligation of income must be carried out based on ability (al-qudrah) and the principle of benefit (maslahah) to maintain a balance between the needs of all family members. Respondents implement financial management strategies such as detailed budgeting, prioritizing urgent expenses, saving, and income diversification. This study confirms that the sandwich generation phenomenon requires social support, financial management education, and a moderate understanding of religion to ensure the sustainability of family. welfare.Keywords: Sandwich generation, muamalah, family economy.